2013
DOI: 10.4049/jimmunol.1203102
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide and Cyclic Adenosine 5′-Monophosphate/Protein Kinase A Pathway Promote IL-9 Production in Th9 Differentiation Process

Abstract: Th9 cells are a novel Th cell subset that produces IL-9 and is involved in type I hypersensitivity such as airway inflammation. Although its critical roles in asthma have attracted interest, the physiological regulatory mechanisms of Th9 cell differentiation and function are largely unknown. Asthma is easily affected by psychological factors. Therefore, we investigated one of the physiological mediators derived from the nervous system, calcitonin gene-related peptide (CGRP), in asthma and Th9 cells because CGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Th9 can be generated from naïve T cell precursors by activation in the presence of TGFβ and IL-4, with IL-4 acting through Signal Transducer and Activator of Transcription 6 (STAT6) (23-25). Alternative cytokines and signaling molecules such as IL-25, IL-1, TSLP, Jagged-2, calcitonin gene-related peptide and the TNF-family member OX40 ligand (OX40L) have been proposed to enhance Th9 differentiation and/or T-cell production of IL-9 (17, 26-30), while cyclooxygenase-2-derived prostaglandins, programmed cell death ligand 2, and 1,25-dihidroxyvitamin D 3 inhibit Th9 polarization (31-33). In addition to murine allergic lung disease, T cell production of IL-9 has been shown to promote T-cell mediated inflammatory eye disease, EAE, colitis, and clearance of intestinal nematode infection (23, 24, 34-38).…”
Section: Introductionmentioning
confidence: 99%
“…Th9 can be generated from naïve T cell precursors by activation in the presence of TGFβ and IL-4, with IL-4 acting through Signal Transducer and Activator of Transcription 6 (STAT6) (23-25). Alternative cytokines and signaling molecules such as IL-25, IL-1, TSLP, Jagged-2, calcitonin gene-related peptide and the TNF-family member OX40 ligand (OX40L) have been proposed to enhance Th9 differentiation and/or T-cell production of IL-9 (17, 26-30), while cyclooxygenase-2-derived prostaglandins, programmed cell death ligand 2, and 1,25-dihidroxyvitamin D 3 inhibit Th9 polarization (31-33). In addition to murine allergic lung disease, T cell production of IL-9 has been shown to promote T-cell mediated inflammatory eye disease, EAE, colitis, and clearance of intestinal nematode infection (23, 24, 34-38).…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al (14) reported that transgenic expression of OX40 in T cells resulted in deterioration of airway inflammation and enhanced Th9 induction in vivo. Mikami et al (15) reported that CGRP promoted allergic asthma and Th9 development through the cAMP/protein kinase A pathway. Using RAMP1-deficient mice that specifically lack CGRP signaling, they also showed partial reduction of IL-9 and amelioration of asthma when these mice were immunized and challenged with OVA.…”
Section: Discussionmentioning
confidence: 99%
“…IL-9 production requires transcription factors including STAT6 (10), GATA3 (8), IFN regulatory factor 4 (IRF4) (11), and PU.1 (12). In addition, the Notch (13) and OX40 signals (14) and the CGRP/cAMP/protein kinase A pathway (15) have been shown to promote Th9 development. These results suggest that various Th2-type transcription factors and additional signals are involved in Th9 development.…”
mentioning
confidence: 99%
“…This suggested that this subset of lymphocytes is a different T-lymphocyte subpopulation characterized by the expression and secretion high amounts IL-9 and IL-10 and hence they were named Th9 lymphocytes. To date, a wide variety of stimuli has been described which contribute to Th9 cell differentiation, as IL-2 [13], IL-25 [50], the peptide related to the calcitonin gene [51], and thymic stromal lymphopoietin [52], among others. This redundancy suggests cell function diversity and heterogeneity.…”
Section: Nkt Cellsmentioning
confidence: 99%